2022
DOI: 10.12669/pjms.39.1.5711
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Correlation and Clinical Significance of T lymphocyte Subsets, IL-6 and PCT in the Severity of Patients with Sepsis

Abstract: Objective: To evaluate the correlation and clinical significance of T lymphocyte subsets, IL-6 and PCT in the severity of patients with sepsis. Methods: One-hundred and twenty patients with sepsis admitted to Baoding No.1 Central Hospital from March 05, 2021 to March 05, 2022 were selected and divided into three groups according to the severity of the disease: the sepsis group, the severe sepsis group and the septic shock group, with 40 cases in each group. The venous blood of all patients was drawn with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…The decrease in T lymphocytes suggests the possibility of immunosuppression. Qian Li et al compared the differences in T lymphocyte subpopulations in different sepsis patients, and the results support the above conclusion [12]. This study incorporated meaningful indicators in univariate analysis into multivariate logistic regression analysis and found that the decrease in CD3+ T cells, the increase in CRP and fever peak are independent risk factors for the occurrence of severe sepsis.…”
Section: Discussionsupporting
confidence: 61%
“…The decrease in T lymphocytes suggests the possibility of immunosuppression. Qian Li et al compared the differences in T lymphocyte subpopulations in different sepsis patients, and the results support the above conclusion [12]. This study incorporated meaningful indicators in univariate analysis into multivariate logistic regression analysis and found that the decrease in CD3+ T cells, the increase in CRP and fever peak are independent risk factors for the occurrence of severe sepsis.…”
Section: Discussionsupporting
confidence: 61%
“…As reported, the absolute counts of CD3+ T cells, CD4+ T cells, CD8+ T cells, B cells, and natural killer cells were associated with clinical prognosis in septic patients. Especially, the CD8+ T cell count was predictive of sepsis progression, and lymphopenia and CD8+ T cell depletion was associated with the clinical outcomes of sepsis [30][31][32]. Here, we did not analyze the association between each lymphocyte subset and clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…T-cell dysfunction is a sign of sepsis immune dysfunction (42). Li et al suggested that for patients with sepsis, severe sepsis, and septic shock, the levels of CD3+, CD4 +, and CD4+/CD8+ decreased significantly with the aggravation of the disease (43). The better the patient recovers after treatment, the higher the levels of CD3+, CD4+, and CD4+/CD8+, and the two are positively correlated.…”
Section: Discussionmentioning
confidence: 99%